2014
DOI: 10.1158/1055-9965.epi-13-0924
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neighborhood and Individual Socioeconomic Status on Survival after Breast Cancer Varies by Race/Ethnicity: The Neighborhood and Breast Cancer Study

Abstract: Background Research is limited on the independent and joint effects of individual- and neighborhood-level socioeconomic status (SES) on breast cancer survival across different racial/ethnic groups. Methods We studied individual-level SES, measured by self-reported education, and a composite neighborhood SES (nSES) measure in females (1,068 non-Hispanic whites, 1,670 Hispanics, 993 African-Americans, and 674 Asian-Americans), aged 18–79 years and diagnosed 1995–2008, in the San Francisco Bay Area. We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 39 publications
4
84
2
Order By: Relevance
“…For the present analysis, we selected specific risk factors that we hypothesized could be associated with E or G activity at the time of blood draw, such as use of menopausal hormone therapy (HT), alcohol intake, body mass index (BMI) (40,41). Individual proportion of Indigenous American genetic ancestry was available for 86 of the 90 samples and was included in the analyses as a proxy for unmeasured sociocultural and/or biological differences.…”
Section: Methodsmentioning
confidence: 99%
“…For the present analysis, we selected specific risk factors that we hypothesized could be associated with E or G activity at the time of blood draw, such as use of menopausal hormone therapy (HT), alcohol intake, body mass index (BMI) (40,41). Individual proportion of Indigenous American genetic ancestry was available for 86 of the 90 samples and was included in the analyses as a proxy for unmeasured sociocultural and/or biological differences.…”
Section: Methodsmentioning
confidence: 99%
“…One important contextual factor is neighborhood socioeconomic status (SES). Area-level measures of SES, including neighborhood SES, have been associated with a variety of health outcomes [2428]. Significant associations have been observed between components of neighborhood SES and breast cancer screening [29], ovarian cancer tumor characteristics [15], and breast [3033], ovarian [34], and prostate [35] cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in breast cancer treatment and outcomes have been documented among Black and White women in the U.S over the past several decades [1][2][3][4][5][6]. Although Black women are less likely to develop breast cancer compared with Whites, once diagnosed, Black women are less likely to receive guideline-adherent treatment [7][8][9][10] and have significantly lower 5-year survival rates [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in cancer treatment and treatment outcomes may partially account for the observed racial and socio-economic disparities in breast cancer mortality [2][3][4][5][6][7][8][9][10][11]. A growing number of studies indicate that African-American women are less likely to undergo breast-conserving surgery (BCS) compared with White women [2,[12][13][14] whereas other studies either reported no difference [15,16] or observed opposite findings [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation